2003
DOI: 10.1136/gut.52.7.953
|View full text |Cite
|
Sign up to set email alerts
|

Duodenal expression of iron transport molecules in untreated haemochromatosis subjects

Abstract: Gut 2003;52:953-959 Background and aims: In HFE associated hereditary haemochromatosis, the duodenal enterocyte behaves as if iron deficient and previous reports have shown increased duodenal expression of divalent metal transporter 1 (DMT1) and iron regulated gene 1 (Ireg1) in affected subjects. In those studies, many patients had undergone venesection, which is a potent stimulus of iron absorption. Our study investigated duodenal expression of DMT1 (IRE and non-IRE), Ireg1, hephaestin, and duodenal cytoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
33
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 47 publications
9
33
1
Order By: Relevance
“…Rather, we showed an inappropriate increase in the level of DMT1 and Ireg1 expression for a given SF level. 22 A preliminary report by Kelleher et al 28 found that untreated subjects with HHC did not have increased DMT1 levels, but phlebotomy therapy resulted in marked increases in DMT1 levels similar to that observed in patients with iron deficiency anemia. The duodenal expression of these iron transporters has been studied in only a few patients with nonhemochromatosis chronic liver disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rather, we showed an inappropriate increase in the level of DMT1 and Ireg1 expression for a given SF level. 22 A preliminary report by Kelleher et al 28 found that untreated subjects with HHC did not have increased DMT1 levels, but phlebotomy therapy resulted in marked increases in DMT1 levels similar to that observed in patients with iron deficiency anemia. The duodenal expression of these iron transporters has been studied in only a few patients with nonhemochromatosis chronic liver disease.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of DMT1 or Ireg1 in the 46 subjects with cirrhosis did not correlate with hemoglobin levels as it did in controls, suggesting that the degree of anemia was not a significant factor causing increased expression of these iron transport genes in cirrhosis. Iron deficiency-an important cause of increased iron absorption and intestinal iron transporter expression 19,22,28 -is common in patients with cirrhosis and frequently is occult. 10,31 Iron deficiency was diagnosed in four subjects with cirrhosis and the expression of the iron transport genes in these four subjects was similar to that observed in the iron-deficient controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to our hypothesis, this finding would indicate that iron absorption is up-regulated more distinctly in patients with hemochromatosis undergoing phlebotomy therapy than in untreated patients. Prior studies showed that intestinal expression of DMT-1 is increased in treated 26 but not in untreated 27 patients with hemochromatosis. Other studies have shown that phlebotomy therapy per se causes a significant increase of intestinal iron absorption in patients with hemochromatosis.…”
Section: Discussionmentioning
confidence: 99%
“…In haemochromatosis duodenal DMT1 and ferroportin expression are raised, leading to excess iron absorption and gradual accumulation of iron. [18][19][20] The recently identified protein hepcidin is central to the pathophysiology of haemochromatosis. Hepcidin is a circulating hormone synthesised in the liver and levels of expression are regulated by iron stores and inflammation.…”
Section: Iron Metabolismmentioning
confidence: 99%